Educação integral e o Colégio de Aplicação da UFS : possibilidades e limites - Silva, Nemesio Augusto Alvares (2016)
This research aims to define indicators of educational quality and evaluate possibilities and limits in the implementation of an Integral Education Project in the College of Application of the Federal University of Sergipe - CODAP. It is a qualitative, non-participatory research, of documentary and bibliographic analysis focused on the historical-analytical construction of the objects of study, which are the Colleges of Application, Integral Education, as public policies for the improvement of education and Quality of Education with the study of its indicators. We analyzed: laws, ordinances, decrees, resolutions, opinions, manuals, management reports and statistical data of the school sense. In addition to a bibliographical survey on the search sites for theses, dissertations and published scientific articles related to the key words. From this study the theoretical reference is presented. First, the Colleges of Application as a public policy created in 1946 to improve teacher training, motivation for its creation, and its development. CFE Opinion No. 292/1962, showing the purposes of the Application Colleges as a field of teaching and experimentation or pedagogic demonstration, its outcomes and ends with the balance of current teaching, research, and extension activities, in addition to of their contributions to programs aimed at improving the quality of basic education. The second reference, Integral Education as a strategy to improve the quality of basic education, its pedagogical conceptions, the historical experiences developed in Brazil as public policies for its implementation. The third referential, is the Quality of Education as a right of all, present in Brazilian educational legislation from the federal constitution of 1988 to the current National Education Plan. We discuss the concepts of Quality Education in the Brazilian educational literature, the main conceptions about quality indicators for education and the adoption of the Initial Quality Student Cost by the National Education Plan. Then, quality indicators for integral education are defined in in-school and out-of-school dimensions. Next, the evaluation methodology is presented with the control protocols, the scale of notes, the scale of concepts of the indicator between potentiator or limiter of the project and the protocols of evaluation with the guiding questions for each of the indicators applied to CODAP. The results of the evaluation are shown and justified, first the indicators of the Intra-school dimension: School Management, School Space, School Time, School Curriculum, Political Pedagogical Project, Faculty and Technical-Administrative Body. And because of the extracurricular dimension, the Financing Policy indicator. In the final considerations the possibilities pointed out by the indicators School Management and Faculty are discussed. The correlation between the School Space, School Time and School Curriculum indicators, which point out the need for a new organization of school work for full-time education, differentiated from the traditional shift organization still predominant in CODAP. And the limits indicated by the indicators Technical-Administrative, Political Pedagogical Project and Financing Policy, for the implementation of a project of Integral Education in the Colleges of Application of UFS.